2022
DOI: 10.3390/ph15050504
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Synthesis of a New Series of 1,2,3-Triazole-Cored Structures Tethering Aryl Urea and Their Highly Selective Cytotoxicity toward HepG2

Abstract: Target cancer drug therapy is an alternative treatment for advanced hepatocellular carcinoma (HCC) patients. However, the treatment using approved targeted drugs has encountered a number of limitations, including the poor pharmacological properties of drugs, therapy efficiency, adverse effects, and drug resistance. As a consequence, the discovery and development of anti-HCC drug structures are therefore still in high demand. Herein, we designed and synthesized a new series of 1,2,3-triazole-cored structures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Silica gel Merck 60 F254 commercial plates were used for analytical TLC together with a UV light to follow the course of the reaction. The structure of all the compounds was confirmed by IR, 1 H NMR (500 MHz) and 13 C NMR spectroscopy (125 MHz). Chemicals shifts (d) are reported in parts per million (ppm) downfield from TMS, J values calculated in Hertz, and the splitting patterns are abbreviated as follows: s, singlet; d, doublet; t, triplet; q, quartet; and m, multiplet.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Silica gel Merck 60 F254 commercial plates were used for analytical TLC together with a UV light to follow the course of the reaction. The structure of all the compounds was confirmed by IR, 1 H NMR (500 MHz) and 13 C NMR spectroscopy (125 MHz). Chemicals shifts (d) are reported in parts per million (ppm) downfield from TMS, J values calculated in Hertz, and the splitting patterns are abbreviated as follows: s, singlet; d, doublet; t, triplet; q, quartet; and m, multiplet.…”
Section: Discussionmentioning
confidence: 94%
“…The 1 H NMR spectra of these acid derivatives also confirmed the proposed structures given that they show one D 2 O exchangeable singlet signal at the d value of B12.60 due to the OH, which is unapplicable for the other probable cyclic pyrrole-2,4-dione products. In the 13 C NMR spectrum of 22, the methyl carbons of both the triazole and hydrazinyl linkers resonated at 10.9 and 10.1 ppm, respectively. In addition, the carbonyl carbon of the thiazolino-4-one ring was observed, as predicted, at 178.0 ppm.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Copper-catalyzed 1,3-dipolar cycloaddition (CuAAC) to form 1,2,3-triazoles is the most popular reaction in click chemistry. Recently, 1,2,3-triazole backbones with hydrogen bonds, moderate dipole moments and enhanced water solubility had been widely used to generate drug candidates of anti-tumor ( Brown et al, 2022 ; Elganzory et al, 2022 ; Mohammed et al, 2022 ; Oekchuae et al, 2022 ; Oliveira et al, 2022 ; Mironov et al, 2023 ), anti-seizure ( Bhattacherjee et al, 2022 ), anti-diabetic ( Dhameja et al, 2022 ), anti-parasitic ( Aljohani et al, 2022 ), anti-bacterial ( Daher et al, 2022 ; Mokariya et al, 2022 ; Nsira et al, 2022 ) and anti-viral ( Kutkat et al, 2022 ; Tatarinov et al, 2022 ) via CuAAC click chemistry ( Figure 1A ).…”
Section: Click Chemistrymentioning
confidence: 99%
“…They found that compound 4 had an IC 50 value of 5.57 μM for HepG2 cells, which was comparable to the positive drug sofosbuvir ( Figure 2 ). It could induce apoptosis in HepG2 cells and showed good affinity, making it a potential anti-liver cancer lead compound ( Chen et al, 2022a ; Oekchuae et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%